2013
DOI: 10.1051/epjconf/20136104013
|View full text |Cite
|
Sign up to set email alerts
|

First Results fromNuSTARObservations of Mkn 421

Abstract: Abstract. Mkn 421 is a nearby active galactic nucleus dominated at all wavelengths by a very broad nonthermal continuum thought to arise from a relativistic jet seen at a small angle to the line of sight. Its spectral energy distribution peaks in the X-ray and TeV γ-ray bands, where the energy output is dominated by cooling of high-energy electrons in the jet. In order to study the electron distribution and its evolution, we carried out a dedicated multi-wavelength campaign, including extensive observations by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 10 publications
7
11
0
Order By: Relevance
“…This agrees with the previous results obtained by many authors (e.g. Abdo et al 2014;Baloković et al 2013;Bartoli et al 2011;Blazejowski et al 2005;Fossati et al 2008;Gaur et al 2012;Lico et al 2014;Richards et al 2013;Smith et al 2008;Ushio et al 2010), who found that there are clear correlations among different energy regimes, and the lower frequencies variations lag behind the higher frequencies variability.…”
Section: Correlation Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…This agrees with the previous results obtained by many authors (e.g. Abdo et al 2014;Baloković et al 2013;Bartoli et al 2011;Blazejowski et al 2005;Fossati et al 2008;Gaur et al 2012;Lico et al 2014;Richards et al 2013;Smith et al 2008;Ushio et al 2010), who found that there are clear correlations among different energy regimes, and the lower frequencies variations lag behind the higher frequencies variability.…”
Section: Correlation Analysissupporting
confidence: 93%
“…Gaur et al 2012;Baloković et al 2013;Abdo et al 2014;Fossati et al 2008;Smith et al 2008;Ushio et al 2010;Bartoli et al 2011;Blazejowski et al 2005;Richards et al 2013). The correlation between the radio, Xray and γ-ray band can be best interpreted by the leptonic models (Giommi et al 1999;Tagliaferri et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fermi-LAT light curve reveals elevated flux with respect to the median, as do the optical and UV data when compared to historical values. Modest soft X-ray flux is apparent from Swift-XRT data in comparison with the long-baseline median (Baloković et al 2013a;Stroh & Falcone 2013) and the intense flaring episodes covered in the literature (e.g., Acciari et al 2009;Tramacere et al 2009;Aleksić et al 2012). Count rates of 10  s −1 in the 0.3-10keV band are up to a factor of 2  Table 8.…”
Section: Multiwavelength Variabilitymentioning
confidence: 82%
“…We first model the NuSTAR spectra for each observation separately, before examining the clear intra-observation spectral variability in Section 3.3 (see Figures 2 and 3, and Baloković et al 2013a). All observation-averaged spectra are shown in Figure 4.…”
Section: Observation-averaged Spectroscopymentioning
confidence: 99%